KERJASAMA KEAMANAN INDONESIA DENGAN AMERIKA SERIKAT MELALUI INDONESIA-UNITED STATES SECURITY DIALOGUE (IUSSD) TAHUN 2014-2018 - Irfan Aufa; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this reasearch is to determine the results of the IUSSD (Indonesian-United States Security Dialogue) 2014-2018 and their impact on improving the security capabilities of the Republic of Indonesia. IUSSD is a security dialogue between Indonesia and the United States that has been held since 2002 until now. The IUSSD dialogue is an effort between the two countries to exchange views and information on security issues and determine the next political policy steps. This dialogue is regularly held by the two countries once a year with alternating locations and times.This study uses a neorealism perspective. In neorealism perspective, the main actor in international relations is the state. For neorealism things that affect the behavior of the states is international structure also anarchy structure. Neorealism called as realism structural. Neorealism recognizes the probability of cooperation between countries. neorealism also emphasizes the acquisition of relative gain in international cooperation. The results showed that the IUSSD is regularly held every year with the main agenda maritime cooperation, countering terrorism, education and training for the TNI, grants for military assistance and the modernization of defense equipment. The IUSSD dialogue has an impact on increasing the security and defense capabilities of the Republic of Indonesia. In the security sector, the IUSSD results have an impact on the increase in counterterrorism, maritime security, and operations to maintain world peace. In the defense sector, the results of IUSSD have an impact on the increase in defense equipment, TNI professionalism (IMET), external military financing (FMF), and the Foreign Military Sales (FMS) program. Keywords: Indonesian-United States Security Dialogue, IUSSD, Militer, TNI.